Erythrocyte Oxidative Status in People with Obesity: Relation to Tissue Losses, Glucose Levels, and Weight Reduction - Beata Szlachta; Anna Birková; Beáta Čižmárová; Anna Głogowska-Gruszka; Paulina Zalejska-Fiolka; Maria Dydoń; Jolanta Zalejska-Fiolka (MDPI AG, 2024)
Background: This study aimed to investigate the impact of reductions in various body mass components on the erythrocyte oxidative status and glycemic state of people with obesity (PWO). Methods: A total of 53 PWO followed a six-month individualized low-calorie diet with exercise, during which anthropometric, biochemical, and oxidative parameters were measured. The participants were divided into groups based on weight (W), visceral fat area (VFA), total body water (TBW), and skeletal muscle mass (SMM) losses, as well as normoglycemia (NG) and hyperglycemia (HG). Results: Weight reduction normalized glycemia and influenced erythrocyte enzyme activity. Regardless of the tissue type lost (VFA, TBW, or SMM), glutathione peroxidase activity decreased in all groups, accompanied by an increase in glutathione reductase activity. Lipofuscin (LPS) and malondialdehyde (MDA) concentrations decreased regardless of the type of tissue lost. The α-/γ-tocopherol ratio increased in those losing >10% body weight, >15% VFA, and >5% TBW. In the NG group, compared to the HG group, there was a decrease in glutathione peroxidase and an increase in glutathione reductase, with these changes being stronger in the HG group. The LPS and MDA concentrations decreased in both groups. Significant correlations were observed between glucose reduction and changes in catalase, retinol, and α-tocopherol, as well as between VFA reduction and changes in vitamin E, L-LPS, and the activities of L-GR and L-GST. Conclusions: This analysis highlights the complex interactions between glucose metabolism, oxidative state, and erythrocyte membrane integrity, crucial for understanding diabetes and its management. This study shows the significant metabolic adaptability of erythrocytes in response to systemic changes induced by obesity and hyperglycemia, suggesting potential therapeutic targets to improve metabolic health in obese individuals.